2017
DOI: 10.1055/s-0042-113459
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Gold Nanoparticles in the Presence of Citrate and Soybean Seed Extract in an Acidic Conditions

Abstract: Through the present study, an eco-friendly method was used to synthesize the gold nanoparticles (GNPs) by using the sodium citrate and extract of the soybean seed as reducing the agents at PH 3. X-Ray diffraction (XRD) method was used to evaluate the crystal structure of as-synthesized NPs and it's revealed that this method leads to well crystallized GNPs. In order to determine the particle size and their distribution, field emission scanning microscopy (FE-SEM) and dynamic light scattering (DLS) were used. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Sodium citrate is a reducing agent for the synthesis of metal nanoparticles, such as gold, silver, copper, and so on. 30 Recently, Gutieŕrez-Serpa et al 31 synthesized gold nanoparticles (AuNPs) by three different reagents, sodium citrate, chloroauric acid, and hydrogen peroxide, and demonstrated that the size of AuNPs was 20−100 nm through measuring the UV spectrum. In this investigation, 100 mL of 0.25 mM chloroauric acid was added into 250 mL volumetric flask and then stirred.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium citrate is a reducing agent for the synthesis of metal nanoparticles, such as gold, silver, copper, and so on. 30 Recently, Gutieŕrez-Serpa et al 31 synthesized gold nanoparticles (AuNPs) by three different reagents, sodium citrate, chloroauric acid, and hydrogen peroxide, and demonstrated that the size of AuNPs was 20−100 nm through measuring the UV spectrum. In this investigation, 100 mL of 0.25 mM chloroauric acid was added into 250 mL volumetric flask and then stirred.…”
Section: Introductionmentioning
confidence: 99%